On the Impact of Digitalization on R&D: R&D practitioners reflect on the range and type of digitalization's likely effects on R&D management. Issue 5 (3rd September 2017) - Farrington, Ted; Alizadeh, Azar
OVERVIEW: Digitalization and Its Implications for R&D Management is an IRI Research platform established to consider the likely impacts of three distinct sets of digitalization technologies—virtual experimentation and simulation, virtual collaboration, and big data—on R&D in the next five years. In October 2016, as a preliminary step in defining its work, platform participants conducted a workshop to gain broad input about the potential impacts of digitalization in the three focus areas. As a result of small-group brainstorming about how each area of digitalization could inform, enable, or disrupt a specific aspect of research and technology management, the research teams identified a number of possible effects of digitalization, including increased consumer and customer intimacy, greater speed to market, broader use of open innovation, leveling of the information playing field across companies, and the growth of true cradle-to-grave product lifecycle simulation.